Heating rate with regard to temperature release of UHPC under cyclic compressive loading. Issue 4 (23rd September 2021) - Deutscher, Melchior; Scheerer, Silke
Abstract: The heating of high‐performance concrete during high‐frequency cyclic loading strongly influences the fatigue strength and has a negative influence on them. This is particularly noticeable in fatigue tests for the standardization of high‐performance concretes. In order to understand the causes and to be able to consider the strength change, effects of different parameters have to be investigated. Both the loading speed and the applied fatigue stress have a strong influence on the speed of heating up. However, from measurements during fatigue tests result curves that show not only the temperature generation but also the temperature release, making it difficult to assess the individual aspects. For this reason, a purely measurement‐based method is being developed with which the cooling can be calculated continuously over the temperature curve and thus the pure heating can be determined. This enables a better understanding of the experiments carried out so far. In this paper, the previous test results are presented, and the evaluation method is explained and applied. This partially corrects the previous understanding of the parameters. The new findings from the evaluation method on the frequency influence are verified and confirmed with three additional tests with thermal insulation.